Very Small Power Plant Transformer Without and With Installation of Neutral Ground Resistance on Relay Operation - Pothisarn, Chaichan; Chiradeja, Pathomthat; Yoomak, Suntiti; Srisuksai, Panu; Ngaopitakkul, Atthapol; Phannil, Natthanon (My University, 2024)
In this study, a double-feeder 22 kV distribution system connected to a very small power plant (VSPP) was simulated in the PowerFactory DIgSILENT program. A neutral ground resistance (NGR) was introduced to reduce a ground fault current from the VSPP, extend the relay operating time to the delay range, and reduce undesired trip of non-faulty feeder that VSPP connected. Thus, the overcurrent protection relay was simulated to analyze working patterns during faults. Three types of VSPP transformer NGR installations were considered: VSPP without NGR, VSPP with a Bisection method approach, and VSPP with the proposed symmetrical component calculation approach. Moreover, this study analyzed the effect of overvoltage on the distribution system with the proposed systematic component calculation approach under fault conditions. The result from the case study indicated that the NGR installation with the proposed approach can reduce the fault current and shift delay time of the protection device to avoid maloperation.
Keywords: Distributed generation (DG); neutral ground resistance; overcurrent protection relay; single-phase fault; very small power plant (VSPP)